PENGARUH UKURAN PERUSAHAAN, RETURN ON ASSET (ROA), LEVERAGE DAN INTENSITAS MODAL TERHADAP TARIF PAJAK EFEKTIF (studi empiris pada perusahaan transportasi yang terdaftar di Bursa Efek Indonesia periode 2011-2013) - Scania Evana Putri; Restu Agusti; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the influence of size, return on asset (ROA), leverage and capital intencity to the effective tax rate. Independent variables used in this study are size, return on asset (ROA), leverage and capital intencity, while the dependent variable in this study is effective tax rate. Populations used in this study is transportation companies listed on IDX 2011-2013, where the total population is used by 15 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 45 (15x3). Data analysis conducted with multiple regression model with help of software SPSS version 20,0. Of the result of the testing that has been done, the partial regression test (t test) showed that the independent variables size, leverage, capital intencity which has a significant influence on effective tax rate, while return on asset (ROA) variables did not influence the effective tax rate.the independent variable can explain dependent variable at 91,6%.Keywords: Size, Return On Asset (ROA), Leverage, Capital Intencity, and Effective Tax Rate.